2017
DOI: 10.1186/s11782-017-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

How do work-family balance practices affect work-family conflict? The differential roles of work stress

Abstract: This paper investigates the relationship between employees' perception of workfamily balance practices and work-family conflicts. It examines the role of challenge stress and hindrance stress as moderators. Based on survey data collected from 841 civil servants in Beijing, we found that perceived work-family balance practices may reduce work-family conflict, while challenge and hindrance work stresses were positively related to work-family conflict. In addition, challenge and hindrance stresses differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…However, the mechanism linking WLBP to intention to leave remains unclear and underdeveloped (Allen, 2001). Most of the existing research demonstrates the direct relationship between WLBP and turnover intention (Chang et al, 2017). A few of the studies focusing on intervening mechanism have shown that work-life balance supportive culture (Cegarra-Leiva et al, 2012) and job embeddedness (Thakur and Bhatnagar, 2017) explain the intervening mechanism between WLBP and turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism linking WLBP to intention to leave remains unclear and underdeveloped (Allen, 2001). Most of the existing research demonstrates the direct relationship between WLBP and turnover intention (Chang et al, 2017). A few of the studies focusing on intervening mechanism have shown that work-life balance supportive culture (Cegarra-Leiva et al, 2012) and job embeddedness (Thakur and Bhatnagar, 2017) explain the intervening mechanism between WLBP and turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…Although work-family conflict is traditionally described using the principles of role theory (Kahn et al, 1964), certainly, the emergence of work-family conflict reflects the competition for an individual's limited resources (time and energy) between work and family role (Chang, Zhou, Wang, & de Pablos Heredero, 2017). However, a limited number of studies have investigated ways of decreasing work-family conflict through the lens of resources.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…However, a limited number of studies have investigated ways of decreasing work-family conflict through the lens of resources. In regard of resource perspective, Conservation of Resources theory-COR model is one of the widely used theories in the workfamily literature (Chang et al, 2017;Haines et al, 2013;Thein, 2014). COR is a general model that covers several stress theories and thus may provide a more appropriate framework for work-family studies to examine both W to FC and F to WC, which are necessary to create a better understanding of work-family conflict comprehensively.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…From the research that has been done, conflicts in Work-Life Balance are more common in women compared to men, women who are married compared to those who are not married, a mother who has a small child experiences conflict with Work-Life Balance more than a mother who has an older child [3]. In a study examining the relationship between gender and Work-Life Balance in terms of dimensions of work disruption and personal life as well as the presence or absence of a significant relationship to the dimensions of personal life disruption with work, get the results that the role of gender is very influential on Work-Life Balance in personal life the cause of which is conflict at work [7], or also called Work-Family Conflict.…”
Section: Introductionmentioning
confidence: 99%